1994
DOI: 10.1088/0953-8984/6/22/001
|View full text |Cite
|
Sign up to set email alerts
|

The high-temperature structure of lead magnoniobate

Abstract: The results of x-ray diffraction measurehens of a lead magnoniobate single crystal-PbMglpNb2/jO3, performed on a four-circle diffractometer with MO Kci radiation. are described. It is'confirmed that even at relatively high temperatures lead ions are shifted from the highaymetry position. It is shown that these shifts are random both in length and direction. A spherical layer model is proposed for the adequate description of the experimental data. The correspondence between the crystal structure and the physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 14 publications
3
36
0
1
Order By: Relevance
“…Namely, as was pointed out in Ref. 27 , a preferable direction of the Pb-shifts can be artificial because of insufficiently high values in (sin θ)/λ (note that we reached (sin θ max )/λ = 0.86Å −1 ). To our opinion, the quality of refinement for the different displacement directions depends on the associated degeneracies: six-fold for the <001>, eight-fold for <111> and twelve-fold for <110>.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Namely, as was pointed out in Ref. 27 , a preferable direction of the Pb-shifts can be artificial because of insufficiently high values in (sin θ)/λ (note that we reached (sin θ max )/λ = 0.86Å −1 ). To our opinion, the quality of refinement for the different displacement directions depends on the associated degeneracies: six-fold for the <001>, eight-fold for <111> and twelve-fold for <110>.…”
Section: Resultsmentioning
confidence: 55%
“…From neutron and X-ray diffraction data, it is known that there is a general tendency that Pb displacements increase as the temperature decreases in complex perovskites (see e.g. 7,25,27 ). One can expect that the observed correlation between the DS intensity and the amplitudes of Pb displacements in PMT may help to create a model which describes short-range order in relaxors.…”
Section: B Possible Description Of the Dsmentioning
confidence: 99%
“…4,16 The thermal evolution of PMR will give rise to a central peak in the Brillouin spectrum due to quasielastic scattering. Such a central peak has been observed by Brillouin scattering in parent relaxor ferroelectrics 1 and solid solutions.…”
Section: Resultsmentioning
confidence: 99%
“…A high temperature X-ray structural study of PMN revealed the positional disorder of Pb 2+ at very high temperatures. 25) Therefore, this situation is possible for PZN. The view held by some authors in attributing the strong Raman modes in the cubic phase to second-order scattering can …”
Section: Raman Spectra At High Temperaturementioning
confidence: 99%